Analisis potensi sumberdaya ikan pelagis kecil di perairan Kota Ambon - Nabila, Aniesa; Totoda, Loana Jeanete (Universitas Halu Oleo, 2023)
Indonesian fisheries are open access, where fishermen can carry out fishing activities in the sea willingly. This factor is an encouragement for fishermen to seize as much fish as possible. The condition, if not utilized properly, can lead to three constraints, namely: low catch rates, low incomes, and excessive capital accumulation in the fishing industry. The potential of pelagic fishery resources was analyzed using the Surplus Production Model (MPS). The production surplus model can be applied if there is a reliable estimate of the total catch or Catch Per Unit Effort (CPUE) and associated fishing effort for the period 2006 – 2015. The regression calculation results in a coefficient value of α= 62.033 and β= -113.031 so that the CPUE regret equation for effort can be written as ht= 62.033 – 113.031, with R2= 0.61 stating that 61% CPUE can be explained by the effort (trip) of catching small pelagic fish. and the remaining 39% is explained by the other factors). Sustainable production at a maximum sustainable yield (MSY) of 9244 tons/year can be achieved if the fishing effort are around 41057 trips. The results of the analysis show that the MSY obtained is 9244 tons/year with an effort (fmsy) of 41057 trips/year and the number of allowable catches (JTB) of 6808.92 tons/year and a potential of 61%